A SOCIO-PRAGMATICS ANALYSIS OF THREATENING ACTS IN THE ACTION MOVIE MANUSCRIPTS - SULASTRI, ASIH (2007)
This research is aimed at describing forms, finding out the speaker's intention, clarifying the politeness strategies, and identifying the reason of employing threatening acts. The data are threatening utterances that are taken from the action movie manuscripts entitled Air Force One, Hostage and Die Hard. In collecting the data, the writer uses observation method by selecting threatening acts, which can be found in those action movie manuscripts. To describe the form the writer refers to the grammatical form. In finding out the speaker's intention the writer uses pragmatic analysis especially locution, illocution, and perlocution. In clarifying the politeness strategies the writer employs Brown and Levinson's politeness strategies. In clarifying the reason, the writer uses SPEAKING Hymens theory. Having analyzed the data, the writer finds that the linguistic forms of threatening which are used in the action movie manuscripts are phrases and sentences. The types of phrase used in the threatening acts are noun phrase and prepositional phrase. While the types of sentences used in the threatening acts are declarative simple sentence, imperative simple sentence, declarative compound sentence, imperative compound sentence, negative imperative simple sentence, negative imperative compound sentence, imperative with let, declarative compound complex sentence and interrogative simple sentence. The speaker's intention of using threatening acts are commanding and threatening. The politeness strategy of the speaker's use on threatening acts are negative politeness strategies and bald on-record strategy. The reasons of the speaker using threatening acts are showing power, showing respects, and preference.